A sustainable approach to individualized disease treatment : The engineering of a multiple use MEMS drug delivery device - Tng, Danny Jian Hang (2013)
Individualized disease diagnosis and therapy has emerged as a new direction in the research of future medication. Over the past several years, innovative approaches based on microelectromechanical system (MEMS) technology have demonstrated promising potential in individualized therapy. In this contribution, a sustainable approach for the individualized treatment of chronic disease is presented using a compact, implantable and refillable MEMS drug delivery device with an electrolysis based actuator. As a demonstration, we utilized the device for programmable delivery of a chemotherapy drug for the treatment of pancreatic cancer with an in vitro configuration based on cancer cell colonies. After the delivery of drug using the device, the growth of the colonies has been greatly inhibited as compared with the control samples. These results show that our new approach has a great potential for future in vivo studies and opens up promising opportunities for future medication.